Developing the Religious Character of Students Through the Practice of Ta’lim Ma’hadi - Fikri Khoirunnisak; Fathor Rahman (Ta'dib, 2025)
This study aims to explore the role of Ta’lim Ma’hadi in strengthening the character of religious students at the Pesantren Putri Al Qodiri Jember. Research this approach using qualitative design studies with intrinsic case studies. Data obtained through observation, participatory interviews, in-depth interviews, and documentation were then analyzed. Research shows that values character instilled religious​ covering faith, obedience, tolerance, and love. The internalization process is marked through three systematic moral stages: moral knowing (the study of scriptures and motivation), moral feeling (exemplary behavior of kyai and ustadz), and moral doing (habituation of worship and practice). Impact practice study, as seen in the regularity of prayer, good ethics, positive moral attitudes, and adherence to religious teachings. Research concludes that the study of Ta’lim Ma’hadi is an instrumental strategy in forming the character of religious students, while also contributing theoretically by connecting modern and traditional moral education with Islamic education.